(untitled) (Revista de Artes Marciales Asiáticas, 2012)
It was the late Bruce Lee who first demonstrated Wing Tsun gongfu’s “sticking hands” (chi-sau) exercise in the US, during the 1964 Long Beach International Karate Championships. Forty-four years later, very few outside of the art truly understand the purpose of chi-sau let alone how it develops tactile reflexes. This article will describe both the fundamental and complex methods of chi-sau training in detail. It will also explain the rationale and theories behind this method as well as discuss a variety of factors that can either improve or retard the acquisition of tactile reflexes.